Evaluation of Medical Malpractice in Urology Cases Resulting in Death - İbrahim Üzün; Bilgin Hösükler; Erdem Hösükler; Buğra Kaan Yazgı (Journal of Contemporary Medicine, 2022)
Aim: This study aimed to present 96 cases evaluated by the 1st Specialization Committee of The Council of Forensic Medicine, which included medical malpractice claims about urologists resulting in death between 2010 and 2015 and to increase the awareness of urologists about medical malpractice claims. Materials and methods: The reports prepared by the 1st Specialization Committee of The Council of Forensic Medicine between 2010–2015 were reviewed retrospectively. All of the cases treated in Urology clinics, alleged medical malpractice, and resulted in death, participated in the study. Results: In this study, 96 cases were included. It was reported that there was medical malpractice in 16 (16.7%) cases. Seventy–six of the patients (79.2%) were female; the most common age range was ≥ 60 years (n:46 47.9%); the mean age was 54,90±19,59 years. Seventy–three (76%) cases were followed up under elective conditions. Complications developed in 20 (20.8%) of the cases during their treatment course. Surgical treatment was applied in 68 (70.8%) patients. Twenty (20.8%) cases were diagnosed with urinary system stone disease and 16 (16.7%) cases with benign prostatic hyperplasia. The committee attributed malpractice to the doctors most frequently due to lack of treatment (n:6, 37.5%). Conclusion: We think that a comprehensive review of the cases with medical malpractice claims will contribute to a better understanding of these cases, the improvement of the medical service provided, and public health.